Distance learning during COVID-19 lockdown: Impact on adolescents with specific learning disorders and their parents - Battisti, Andrea; Lazzaro, Giulia; Varuzza, Cristiana; Vicari, Stefano; Menghini, Deny (Frontiers in Psychiatry, 2022)
Background The transition of teaching from in-person to Distance Learning (DL) due to the COVID-19 pandemic led to negative effects on students' psychological wellbeing and academic achievement. The worst consequences have been experienced by students with so-called special educational needs, as well as by their parents. However, very little emphasis has been placed on the effects of DL in students with Specific Learning Disorders (SLD). The present work aimed to evaluate the effects of DL during the COVID-19 lockdown in Italian students with SLD and in their parents. Methods An online survey was administered to 92 students with SLD and their parents after the COVID-19 lockdown. The survey consisted of four sections: participants' demographic information; perceived stress related to general aspects (i.e., social and family determinants) as well as specific aspects related to DL; attitudes and feelings toward DL; and academic grades before and after DL. Results Students with SLD perceived stress mainly from social isolation/distancing and DL (p always ≤ 0.0001), especially from online classes and oral exams (p always ≤ 0.0001). Students who did not benefit from appropriate accommodations (i.e., individualized teaching and learning methods) during DL perceived 3 times more DL-related stress than those who used them as in-person learning (OR = 3.00, CI 95%: 1.24–7.28, p = 0.015). Girls perceived more stress from online lessons (OR = 0.40, CI 95%: 0.16–0.96, p = 0.04) and use of devices (OR = 0.33, CI 95%: 0.14–0.80, p = 0.015) than boys. Negative feelings (less motivation, reduced ability to understand lessons, interact, and stay focused) and positive feelings (less anxiety and more self-confidence with its own rate of learning) toward DL emerged. Higher academic grades also was observed after DL (p ≤ 0.0001). Lastly, strong and positive correlations emerged between students' and parents' perceived stress during DL (p always < 0.001). Implications The present study prompts special considerations for students with special educational needs not only when providing conventional instruction, but especially when it is necessary to suddenly modify teaching approaches.